Selective list of the Catalogues of the VIR Global Collection on potato published in 1963–2018 - article Editorial (Труды по прикладной ботанике, генетике и селекции)
Catalogues of the VIR Global Collection on potato published in 1963-2018. For the sake of convenience, the material is arranged in chronological order. It is our hope that the list will be found useful by our readers and authors of scientific publications. The list was compiled by the staff of the Library and Publishing Department of VIR.